Analysis of Eddy Current Density using ANSYS MAXWELL Software - Jumaat, Siti Amely; Ahamad, Muhammad Nassier (Journal of Electronic Voltage and Application, 2020)
This paper are proposed the simulation of eddy current density  over the non-ferrous materials. Correlation between  that circulating in non-ferrous magnetic material can stimulate the suspension force. Some simulation have been done using Finite Element Method (FEM) that provided in ANSYS Maxwell simulator software in order to illustrate the formation of . The 3-dimensional shape of current-carrying coil suspended 1cm over non-ferrous conductor is sketch up to emphasize or illustrate the existence of vertical magnetic forces. From simulation, the productivity of  was clearly appears on the top of conductorâ€™s surface whose interpretation from a current-carrying coil reaction. The causality is dependently on conductor properties, input frequency of current AC source, and conductor thickness that supposedly influence the amount of . From simulation shown the higher thickness and frequency of AC current will encourage the formation of . It also can conclude the high magnetization enable to conduct more .